Protective effect and mechanism of Xiaoyu Xiezhuo decoction on ischemia–reperfusion induced acute kidney injury based on gut–kidney crosstalk - Yue Ji; Yunming Xiao; Shipian Li; Yihua Fan; Yuzi Cai; Bo Yang; Hongbo Chen; Shouci Hu (Renal Failure)
This study aimed to explore the mechanism of Xiaoyu Xiezhuo decoction (XXD) on ischemia–reperfusion-induced acute kidney injury (IRI-AKI) using network pharmacology methods and gut microbiota analysis. A total of 1778 AKI-related targets were obtained, including 140 targets possibly regulated by AKI in XXD, indicating that the core targets were mainly enriched in inflammatory-related pathways, such as the IL-17 signaling pathway and TNF signaling pathway. The unilateral IRI-AKI animal model was established and randomly divided into four groups: the sham group, the AKI group, the sham + XXD group, and the AKI + XXD group. Compared with the rats in the AKI group, XXD improved not only renal function, urinary enzymes, and biomarkers of renal damage such as Kim-1, cystatin C, and serum inflammatory factors such as IL-17, TNF-α, IL-6, and IL 1-β, but also intestinal metabolites including lipopolysaccharides, d-lactic acid, indoxyl sulfate, p-cresyl sulfate, and short-chain fatty acids. XXD ameliorated renal and colonic pathological injury as well as inflammation and chemokine gene abundance, such as IL-17, TNF-α, IL-6, IL-1β, ICAM-1, and MCP-1, in AKI rats via the TLR4/NF-κB/NLRP3 pathway, reducing the AKI score, renal pathological damage, and improving the intestinal mucosa’s inflammatory infiltration. It also repaired markers of the mucosal barrier, including claudin-1, occludin, and ZO-1. Compared with the rats in the AKI group, the α diversity was significantly increased, and the Chao1 index was significantly enhanced after XXD treatment in both the sham group and the AKI group. The treatment group significantly reversed this change in microbiota.